1997
DOI: 10.1046/j.1365-2141.1997.3283145.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of oral anticoagulant therapy in lupus anticoagulant positive patients with the anti‐phospholipid syndrome

Abstract: Introduction of the International Normalized Ratio (INR) has improved the standardization of laboratory control of oral anticoagulant therapy (OAT). However, it has been reported that misleading INR results can be obtained from OAT patients with lupus anticoagulant (LA). To investigate this claim, we studied 35 OAT patients, 14 of whom had anti‐phospholipid syndrome (APS) with a documented LA. Attainment of anticoagulation was confirmed by chromogenic assay of factor VII and factor X. Prothrombin times were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 22 publications
0
47
0
3
Order By: Relevance
“…Measuring factor Xa activity with the CFX assay may therefore provide benefits to APS patients because the test results are not influenced by the presence of APL. To date, few studies have compared INR values and factor X activities in patients with and without APS [10][11][12][13][14]. The patient number in some studies was only small [12,13], and the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring factor Xa activity with the CFX assay may therefore provide benefits to APS patients because the test results are not influenced by the presence of APL. To date, few studies have compared INR values and factor X activities in patients with and without APS [10][11][12][13][14]. The patient number in some studies was only small [12,13], and the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…If the problems with the INR in patients with lupus anticoagulants on warfarin therapy are not taken into account, however, this study will potentially yield inconclusive results. In our recent paper (Lawrie et al, 1997) Valle et al (1996), who they say reported marked discrepancies in patients with LA on OAT, despite local determination of ISI. In fact, these workers used a different system, with diluted plasmas and Pro-IL complex, which is combined thromboplastin reagent and contains absorbed bovine plasma, which in theory could create artefacts or LA cofactor-like phenomena.…”
Section: Monitoring Oral Anticoagulant Therapy In Patients With Lupusmentioning
confidence: 99%
“…Lawrie et al (1997) reported that use of a locally assigned International Sensitivity Index (ISI) reduced the variation in International Normalized Ratio (INR) results obtained with different thromboplastins in patients with lupus anticoagulants on warfarin therapy. They also observed a similar decrease in variation for patients without lupus anticoagulants on warfarin therapy, and suggested that one problem with using the INR to monitor warfarin therapy in patients with lupus anticoagulants was related to the use of 'generic' ISI values (Lawrie et al, 1997). This suggestion does not explain the observations of Della- Valle et al (1996), however, who found marked INR discrepancies in patients with lupus anticoagulants on warfarin therapy, in spite of the use of locally determined ISIs.…”
Section: Epidemiology Of Monoclonal Gammopathy In Cote D'or Francementioning
confidence: 99%
“…Della Valle and collaborators found INRs obtained with a recombinant thromboplastin (Recombiplastin, Ortho Laboratories) to be significantly higher in lupus anticoagulant (LA)-positive, than in LA-negative patients, using the manufacturer's instrumentcertified ISI, and questioned the validity of the INR system for monitoring OAT in LA-positive patients (158). Reagentdependent thromboplastin sensitivity to LA was also reported in three later studies (159)(160)(161). Laboratory and patient-specific determinations of the effect of LAs on thromboplastin sensitivity, and the avoidance of reagents that show an LA influence is one solution to this problem.…”
Section: Patient Factors Influencing Thromboplastin Sensitivitymentioning
confidence: 69%